2023
DOI: 10.2174/0929867329666221006115329
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Novel Therapeutic Uses of Alpha Lipoic Acid

Abstract: Alpha-lipoic acid (ALA) is a potent antioxidant used in the management of diabetic neuropathy due to its ability to prevent neuronal lipid peroxidation. ALA also chelates transition metals, which can be beneficial in some diseases related to metal overload. Because of its unique antioxidant properties, ALA has potential novel applications in other diseases related to oxidative stress and inflammation. This review summarizes aspects of recent clinical trials in addition to the well described uses to manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…[ 156 ] It can also synergistically collaborate with other antioxidants, such as vitamins C and E, augmenting cellular antioxidant processes. [ 157 ] Notably, ALA showcases the ability to chelate metal ions (such as copper, iron, and zinc), forming complexes to alleviate detrimental oxidative processes. [ 158 ] Furthermore, ALA can activate the Nrf2 signaling pathway, thereby stimulating the production of antioxidant enzymes, including SOD and GPx.…”
Section: Design Strategies and Applications Of Antioxidant Hydrogelsmentioning
confidence: 99%
“…[ 156 ] It can also synergistically collaborate with other antioxidants, such as vitamins C and E, augmenting cellular antioxidant processes. [ 157 ] Notably, ALA showcases the ability to chelate metal ions (such as copper, iron, and zinc), forming complexes to alleviate detrimental oxidative processes. [ 158 ] Furthermore, ALA can activate the Nrf2 signaling pathway, thereby stimulating the production of antioxidant enzymes, including SOD and GPx.…”
Section: Design Strategies and Applications Of Antioxidant Hydrogelsmentioning
confidence: 99%
“…Alpha-Lipoic acid (ALA) is an endogenous antioxidant derived from octanoic acid, which is found in various foods of animal or vegetable origin. It has a high antioxidant capacity, acting in multiple ways to reduce oxidative stress, among which it has been reported that it acts as a radical scavenger and ionic metal chelator, promotes the synthesis of GSH and recycles other antioxidants such as vitamin C, vitamin E, and coenzyme Q10 (CoQ10) [ 345 ]. In addition, this antioxidant has an amphipathic nature, which allows it to act both at the extracellular and intracellular levels.…”
Section: Antioxidants Treatments For Aging Related Diseasesmentioning
confidence: 99%
“… 3 Moreover, it has great therapeutic potential in managing numerous clinical conditions, including anti-cancer, anti-HIV, anti-inflammatory, and anti-AD treatments. Some reviews have summarized the biological activities and therapeutic potentials of ALA. 4 …”
Section: Introductionmentioning
confidence: 99%